Vpliv mase jekla in vrste sredstev za gašenje na mehanske lastnosti jekla - Grum, Janez (Kovine zlitine tehnologije, 1999)
Mechanical properties of a machine part depend on the kind of steel used and heat treatment applied. To this end various methods of determination of through-hardenability of steels, such as Jominy and Grossmann methods, have been developed. The Jominy hardenability curves have made it possible to set up appropriate criteria of evaluation of through-hardenability and mutual comparison of steels. Lamont and Assimow designed special diagrams which enable an engineer to prescribe a suitable high-tempering temperature for heat-treatment steels ensuring the desired mechanical properties with respect to the mass of the machine part and intensity of the cooling medium. The paper presents regarding cooling intensities of some oils of domestic production and of polymeric water solutions. Numerous temperature measurements on heat-treatment steel specimens with different masses were made. They provided very important information on cooling rates for a material when using different quenching agents. The cooling rates attained for a steel permit, for a given steel with a known continuous cooling diagram, determination of microstructural changes, and consequently prediction of mechanical properties of the steel.
Keywords: jekla; gašenje; mehanske lastnosti; trdota; kaljenje